ANALYSIS OF THE IMPACT OF IMPROVING COAL PRODUCTION ON ECONOMIC STRUCTURE OF KABUPATEN MUARA ENIM, SOUTH SUMATERA - triswan suseno (STATISTIKA: Forum Teori dan Aplikasi Statistika, 2019)
Starting in 2022, the State-owned coal company in South Sumatera plans to produce coal 5.72 million tonnes per year. 3.43 million tons of which will be processed to produce 450,000 tons of polypropylene, 1.47 million tons to produce 400,000 tons of dymethyl ether, and 811,885 tons to produce 570,000 tons of urea fertilizer. The amount of coal to steam power plant needs as much as 3.45 million tons, bringing the total addition of coal production per year as much as 9.17 million tons.The coal downstreaming sector will able to absorb labour of 1,604 people, the size of the value of money which will be obtained by these workers is estimated at USD 26,459,273, an the company's profit from the results of the processing of the coal downstreaming of USD 298,476,000. The existence of the industry turned out taxes, generating government revenue to USD 110.819.765. Using input output method, the increase in coal production amounted to 9.1 million tonnes or IDR 3.44 trillion worth encourages other sectors to improve the output of Rp. 3.62 trillion. The impact of investment for processing coal in Muara Enim in 2022 results on increasing of MuaraEnim GDP to IDR 114,38 trillion and creating jobs for the various sectors as much as 5,578 people.Keywords: GDP, coal, downstream, input, output.